Antidiabetic Activity of Curcuma mangga Val. Rhizome Ethyl Acetate Fraction against Mice Induced by Alloxan (JURNAL PROTEKSI KESEHATAN, 2021)
The rhizome of the temu mangga is a member of the Zingiberaceae family that has been used since ancient times for treatment of diabetes. The aim of this study was to examine the activity of reducing blood glucose levels in diabetic mice induced by alloxan after administration of the ethyl acetate fraction of temu mangga rhizome at a dose of 100; 200 and 300 mg/KgBW were compared with negative control (Na CMC) and positive control (Glibenclamide 0.65 mg/Kg BW). The research data were statistically analyzed using two-way ANOVA for the parameters of the percentage decrease in blood glucose and the percentage change in body weight followed by the Tukey multiple range test. The results showed that the administration of the ethyl acetate fraction of the mangga rhizome at doses of 100, 200 and 300 mg/KgBW prevented weight loss in mice compared to negative controls (p